2018
DOI: 10.1007/s10676-018-9460-x
|View full text |Cite
|
Sign up to set email alerts
|

Power influences upon technology design for age-related cognitive decline using the VSD framework

Abstract: Implicit in the value sensitive design (VSD) approach is a concern for understanding, and where possible, disrupting problematic power relationships. Yet an awareness of the issues and ethics of power relations is a prerequisite for such a concern to bear fruit. This article provides some insight into the issues, and through a case study of technology design to support care arrangements for age-related cognitive decline, illustrates how finding a satisfactory resolution can be particularly troublesome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…They remind us that even in these settings, "[d]esign needs to be clear about the exercise of power. For the technological designer, it should always be as intentional as possible, rather than allowing power to be exercised in an intuitive or unconscious manner" [7]. We imagine, given the enthusiasm for AI applied to social problems, that it's not difficult for designers to become complicit in promoting those understudied technologies that may worsen the problem of isolation, such as certain AI-based companion robots described as "problematic" by some domain experts [8].…”
Section: Design Questions From the Health Sciencesmentioning
confidence: 99%
“…They remind us that even in these settings, "[d]esign needs to be clear about the exercise of power. For the technological designer, it should always be as intentional as possible, rather than allowing power to be exercised in an intuitive or unconscious manner" [7]. We imagine, given the enthusiasm for AI applied to social problems, that it's not difficult for designers to become complicit in promoting those understudied technologies that may worsen the problem of isolation, such as certain AI-based companion robots described as "problematic" by some domain experts [8].…”
Section: Design Questions From the Health Sciencesmentioning
confidence: 99%
“…As a thought experiment the attento proves very useful for gleaning what attitudes to future care robots might be, and what problems might arise. Value sensitive design (VSD), as argued elsewhere [12], needs to take better account of social power, and adopt some normative positions concerning which values the model itself values most highly. The notion of computational 'consciousness,' like so many terms in the world of computing (e.g.…”
Section: The Attento Modelmentioning
confidence: 99%
“…Researchers at Florida state university "surveyed 445 people between the ages of 80 and 93 and found that most of the adults over 80 are using technological gadget [s] daily" [11]. Although ethical considerations in relation to technology-based care of the elderly have been the subject of numerous studies [12][13][14][15][16][17], relatively little has been considered regarding care robots [18,19] and the integration of complex robots into care for the elderly. One particular month long social robot study revealed that the acceptance care robots depends on factors from social and psychological usage context, one of the former being trust [20].…”
Section: Introductionmentioning
confidence: 99%
“…It is social context that gives rise to meaningful privacy, regardless of whether that context is the blockchain or in a grocery store. Here, privacy is understood to be an intrinsic and pliant feature of social contexts, shaped by social contexts and to a lesser extent, shaping of social contexts (Burmeister, 2016;Burmeister & Kreps, 2018;Teipel et al, 2016;Wahlstrom, Fairweather, & Ashman, 2017) and therefore we define privacy as Privacy is a highly contextual social good which is instrumental to the perpetuation of other social goods. People exercise privacy through personal information preferences and practices which are specific to social contexts and changing over time.…”
Section: Introductionmentioning
confidence: 99%